Genetic studies of an Escherichia coli K-12 temperature-sensitive mutant defective in membrane protein synthesis. - Sato, T (1979)
The mutant divE42(Ts) of Escherichia coli K-12, defective in the synthesis of membrane proteins and in the transcription of the lac operon at high temperature, has been further characterized. It was found that a mutation (divE42) located at about min 22 on the E. coli chromosome map is responsible for the Lac- phenotype and temperature-sensitive growth. The mutation could be contransduced with serC, pyrD, or pyrC by phage P1 at a frequency of 4, 16, or 0.5%, respectively, the gene order being serC-pyrD-ompA-sulA-divE-pyrC. Examination of temperature-independent revertants and Pyr+ transductants revealed that all the mutant phenotypes examined (deficiencies in the increase of activities of some membrane enzymes, expression of the lac operon, and synthesis of several other proteins) are due to a single mutation (divE42) which is recessive to the wild-type (divE+) allele. Protein synthesis in the mutant was also analyzed by dodecyl sulfate-polyacrylamide gel electrophoresis. Synthesis of a number of proteins, including membrane proteins, was found to decrease significantly, whereas that of an elongation factor, EF-Tu, increased upon transfer of a log-phase culture to high temperature (42 degrees C). These effects of temperature shift-up on protein synthesis were evident within 5 min under the conditions used.